Stability of custom-designed photoreactor for photocatalytic oxidation of Reactive Black 5 dye using zinc oxide - Lee, Kian Mun; Lai, Chin Wei; Juan, Joon Ching (Taylor & Francis, 2018)
In this study, advanced photocatalytic oxidation of Reactive Black 5 (RB5) dye as the model pollutant was investigated using zinc oxide (ZnO) particles as an active photocatalyst in our custom-designed photoreactor. The ZnO particles were characterised to investigate its physical and chemical properties. Several crucial processing parameters that affect the photodegradation efficiency in our custom-designed photorector were studied in detail, such as amount of ZnO loaded, initial concentration of RB5 dye and solution pH. In the final stage of our study, Langmuir–Hinshelwood model was adopted to determine the rate constant of RB5 dye photocatalytic degradation. Based on our experimental results, it was found that the degradation efficiency was increased significantly with increasing the amount of ZnO particles up to 0.03 g and applied low concentrations of 40 ppm RB5.